Field Symptoms of Boron Toxicity and Deficiency in Florida Peanuts - Jacque W. Breman; William D. Thomas; Henry E. Jowers; Rao S. Mylavarapu (EDIS)
Boron is an essential micronutrient needed by peanut to prevent “hollow heart” and to provide for sufficient plant growth, but it can be a challenge to manage for peanut production on sandy soils. There may be times when peanut growers, extension agents, and consultants find field symptoms when either boron toxicity or boron deficiency is the cause of peanut yield loss and low kernel quality. This 4-page fact sheet reviews the boron management strategy in Florida, presents information on boron sufficiency and toxicity levels from the literature, and provides photographs of field symptoms that can be used by growers and extension agents. Written by J. W. Breman, W. D. Thomas, H. E. Jowers, and R. S. Mylavarapu, and published by the UF Department of Soil and Water Science, May 2012.